Knowledge and awareness of oral cancer patients regarding its etiology, prevention, and treatment - Sanjul Lakra; Gurkiran Kaur; Abhishek Mehta; Vivek Kaushal; Rajeev Atri; Sunder (Wolters Kluwer Medknow Publications, 2020)
Introduction: Assumption on part of healthcare workers that individuals suffering from oral cancer are usually aware of the reasons why they got the disease can lead to creation of a knowledge deficit group and may increase chances of relapse and complications in future. Methodology: An interview-based questionnaire study was conducted on 218 patients with oral cancer admitted for treatment at a Regional Cancer Centre (RCC) in north India. Questions were designed to assess their knowledge and awareness regarding etiology, treatment, and prevention of oral cancer. Results: The majority of the study participants were from lower and lower middle socioeconomic class. Most of them were not aware about early signs of oral cancer. Some of them were still continuing with the habit of tobacco consumption. Conclusion: There is an urgent need to improve the knowledge level of oral cancer patients for its primary and secondary prevention.